Analysis of microbial community, physiochemical indices, and volatile compounds of Chinese te‐flavor baijiu daqu produced in different seasons. (3rd June 2021) - Fu, Gui‐Ming; Deng, Meng‐Fei; Chen, Yan; Chen, Yan‐Ru; Wu, Sheng‐Wen; Lin, Pei; Huang, Bing‐Jing; Liu, Cheng‐Mei; Wan, Yin
Abstract: BACKGROUND: Chinese te ‐flavor baijiu (CTF), the most famous Chinese baijiu in Jiangxi province, China, is made from a unique daqu . Its characteristic style is closely related to the daqu used for fermentation. However, current studies on the effects of different production seasons on microbial communities, physicochemical indices, and volatile compounds in CTF daqu are very rare. RESULTS: The relationships of microbial communities, physicochemical indices, and volatile compounds in CTF daqu produced in summer (July and August) and autumn (September and October) were studied. The results of Illumina MiSeq sequencing indicated that there was greater bacterial diversity in the CTF daqu ‐7 (produced in July) and CTF daqu ‐8 (produced in August) and greater fungal diversity in the CTF daqu ‐9 (produced in September) and CTF daqu ‐10 (produced in October). The physicochemical indices of CTF daqu produced in different seasons were significantly different. It was determined that CTF daqu ‐9 had the highest esterification and liquefaction abilities. A total of 44 volatile compounds, including alcohols, esters, aldehydes, and ketones were identified in CTF daqu produced during different seasons. Among them, CTF daqu ‐9 had the greatest alcohol content. CONCLUSION: September (early autumn) is the best production period for CTF daqu . The results of the study provide a theoretical basis for the standardized and uniform production of Chinese baijiu . © 2021 Society of Chemical Industry.